Micronized purified flavonoid fraction for the treatment of chronic venous insufficiency, with a focus on postthrombotic syndrome: A narrative review. Issue 4 (8th May 2021) - Li, Ke Xuan; Diendéré, Gisele; Galanaud, Jean‐Philippe; Mahjoub, Nada; Kahn, Susan R.
Abstract: Introduction: Postthrombotic syndrome (PTS) is a form of secondary chronic venous insufficiency (CVI) that occurs after deep vein thrombosis (DVT). Effective treatments for PTS are lacking. Micronized purified flavonoid fraction (MPFF) is a venoactive drug used in the treatment of CVI. Objective: To determine whether MPFF is a good candidate to explore as a therapeutic agent for PTS. Methods: We performed a narrative review in which we identified 14 systematic reviews, 33 randomized controlled trials, and 19 observational studies that discussed the use of MPFF in CVI, as well as studies that reported on the mechanistic action of MPFF in relation to the pathophysiology of PTS. Results: MPFF targets a number of pathophysiologic components of PTS. Based on animal models and human studies investigating objective vascular and lymphatic measures, MPFF promotes venous recanalization after DVT, decreases venous remodeling and reflux, inhibits inflammatory processes, improves venous tone and stasis, improves lymphatic circulation, improves capillary hyperpermeability, and decreases tissue hypoxia. Furthermore, MPFF shows promise in improving clinical manifestations, quality of life, and objective venous parameters of CVI. Studies suggest good patient acceptability and tolerability with the use of MPFF in CVI. Conclusion: MPFF is a good candidate to explore as a potential therapy for PTS. Confirmatory high‐quality studies are still needed to reinforce the evidence supporting the use of MPFF in CVI. Double‐blind randomized controlled trials with clinical endpoints are needed to assess the clinical efficacy of MPFF in the treatment of PTS.